2007
DOI: 10.1111/j.1365-313x.2007.03234.x
|View full text |Cite
|
Sign up to set email alerts
|

A hydraulic signal in root‐to‐shoot signalling of water shortage

Abstract: SummaryPhotosynthesis and biomass production of plants are controlled by the water status of the soil. Upon soil drying, plants can reduce water consumption by minimizing transpiration through stomata, the closable pores of the leaf. The phytohormone abscisic acid (ABA) mediates stomatal closure, and is the assigned signal for communicating water deficit from the root to the shoot. However, our study does not support ABA as the proposed long-distance signal. The shoot response to limited soil water supply is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

19
339
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(368 citation statements)
references
References 45 publications
19
339
1
9
Order By: Relevance
“…In these plants, ABA is produced via the residual activity of defective enzymes (Rock and Zeevaart, 1991) or via minor ABA biosynthetic pathways hypothesized to exist in higher plants (North et al, 2007). With regard to the location of ABA synthesis, shoots are the main source of ABA in the plant, as found in grafting studies (Holbrook et al, 2002;Christmann et al, 2007;McAdam et al, 2016a) and also supported by gene expression data (Ernst et al, 2010;Boursiac et al, 2013;Kuromori et al, 2014). The leaf-borne ABA is synthesized mainly in the phloem companion cells of the vasculature (Endo et al, 2008;Kuromori et al, 2014).…”
mentioning
confidence: 59%
“…In these plants, ABA is produced via the residual activity of defective enzymes (Rock and Zeevaart, 1991) or via minor ABA biosynthetic pathways hypothesized to exist in higher plants (North et al, 2007). With regard to the location of ABA synthesis, shoots are the main source of ABA in the plant, as found in grafting studies (Holbrook et al, 2002;Christmann et al, 2007;McAdam et al, 2016a) and also supported by gene expression data (Ernst et al, 2010;Boursiac et al, 2013;Kuromori et al, 2014). The leaf-borne ABA is synthesized mainly in the phloem companion cells of the vasculature (Endo et al, 2008;Kuromori et al, 2014).…”
mentioning
confidence: 59%
“…Therefore, ABA-GE was proposed to be a rootto-shoot signaling molecule. However, under drought stress, ABA-mediated stomatal closure occurs independently of root ABA biosynthesis (Christmann et al, 2007). Thus, the involvement of ABA-GE in root-to-shoot signaling of water stress conditions remains to be revealed (Goodger and Schachtman, 2010).…”
mentioning
confidence: 99%
“…The stomatal aperture was correlated with the ABA content in the xylem sap, suggesting that ABA synthesized in roots was transported to leaves via the xylem to induce stomatal closure. Nevertheless, it appears that ABA transport from roots to leaves is not always required for stomatal closure, because reciprocal grafting between WT and ABA-deficient mutants showed that leaf genotypes, but not root genotypes, were correlated with leaf stomatal conductance (12,13).…”
mentioning
confidence: 99%